Workload of Healthcare Workers During the COVID-19 Outbreak in Korea: A Nationwide Survey - Cheong, Hae Suk; Kwon, Ki Tae; Hwang, Soyoon; Kim, Shin-Woo; Chang, Hyun-Ha; Park, Se Yoon; Kim, Bongyoung; Lee, Shinwon; Park, Jiho; Heo, Sang Taek; Oh, Won Sup; Kim, Yeonjae; et al. (Journal of Korean medical science, 2022)
As the coronavirus disease 2019 (COVID-19) pandemic is ongoing, heavy workload of healthcare workers (HCWs) is a concern. This study investigated the workload of HCWs responding to the COVID-19 outbreak in South Korea. A nationwide cross-sectional survey was conducted from September 16 to October 15, 2020, involving 16 healthcare facilities (4 public medical centers, 12 tertiary-care hospitals) that provide treatment for COVID-19 patients. Public medical centers provided the majority (69.4%) of total hospital beds for COVID-19 patients (n = 611), on the other hand, tertiary care hospitals provided the majority (78.9%) of critical care beds (n = 57). The number of beds per doctor (median [IQR]) in public medical centers was higher than in tertiary care hospitals (20.2 [13.0, 29.4] versus 3.0 [1.3, 6.6], = 0.006). Infectious Diseases physicians are mostly (80%) involved among attending physicians. The number of nurses per patient (median [interquartile range, IQR]) in tertiary-care hospitals was higher than in public medical centers (4.6 [3.4-5] vs. 1.1 [0.8-2.1], = 0.089). The median number of nurses per patient for COVID-19 patients was higher than the highest national standard in South Korea (3.8 vs. 2 for critical care). All participating healthcare facilities were also operating screening centers, for which a median of 2 doctors, 5 nurses, and 2 administrating staff were necessary. As the severity of COVID-19 patients increases, the number of HCWs required increases. Because the workload of HCWs responding to the COVID-19 outbreak is much greater than other situations, a workforce management plan regarding this perspective is required to prevent burnout of HCWs.